A Liquid Gripper Based on Phase Transitional Metallic Ferrofluid (Adv. Funct. Mater. 32/2021). (10th August 2021) - Wang, Hongzhang; Chen, Sen; Li, Haowei; Chen, Xianzhe; Cheng, Jiashu; Shao, Yunlin; Zhang, Chenglin; Zhang, Jie; Fan, Linlin; Chang, Hao; Guo, Rui; Wang, Xuelin; et al.
Abstract : Liquid Gripper In article number 2100274, Liang Hu, Yen Wei, Jing Liu, and co‐workers present a magnetic liquid gripper based on a metallic ferrofluid that enables intimate contact with arbitrarily shaped objects and then generates a strong adhesion force upon solidification, which can be reversibly eliminated by moderate melting. Through coupling the magnetism of metallic ferrofluid and switchable adhesion force to objects, any non‐magnetic targets can be manipulated via an applied magnetic field.